Relationship between ISO 9001 certification maturity and EFQM business excellence model results - Fonseca, Luís (2015)
Purpose: This exploratory research evaluates if there is a relationship between the number of years since an organization has achieved ISO 9001 certification and the highest level of recognition received by the same organization with the EFQM Business Excellence Model. Methodology/Approach: After state of the art review a detailed comparison between both models was made. Fifty two Portuguese organizations were considered and Correlation coefficient Spearman Rho was used to investigate the possible relationships. Findings: Conclusion is that there is indeed a moderate positive correlation between these two variables, the higher the number of years of ISO 9001 certification, the higher the results of the organization EFQM model evaluation and recognition. This supports the assumption that ISO 9001 International Standard by incorporating many of the principles present in the EFQM Business Excellence Model is consistent with this model and can be considered as a step towards that direction. Research Limitation/implication: Due to the dynamic nature of these models that might change over time and the possible time delays between implementation and results, more in-depth studies like experimental design or a longitudinal quasi-experimental design could be used to confirm the results of this investigation. Originality/Value of paper: This research gives additional insights on conjunct studies of both models. The use of external evaluation results carried out by the independent EFQM assessors minimizes the possible bias of previous studies accessing the value of ISO 9001 certification.